Perkembangan Cara Berpikir Ilmiah di Barat dan Relevansinya terhadap Paradigma Pendidikan Islam - Balkis, Lutfiah Holifa; Amri Saputra; Winda Islamitha Nurhamidah; Maesaroh, Maesaroh; David Ricardo; Usman, Usman (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
This study examines the historical development of scientific thinking in the West and its relevance to Islamic education through a qualitative library research design combined with a systematic literature review. The review covered studies published between 2014–2024 and collected through major databases such as Scopus, Web of Science, DOAJ, Google Scholar, and Moraref, resulting in a synthesis of 72 relevant publications. The analysis identifies significant epistemological shifts from classical rationalism to contemporary pluralism and evaluates their implications for Islamic education. The study formulates an operational framework of reason–revelation integration that can be applied in curriculum design, particularly in strengthening critical inquiry, ethical reasoning, and spiritual orientation. The findings highlight the potential of epistemological integration to enrich Islamic education and address the challenges posed by modern scientific paradigms.